The hostile hospital - Snicket, Lemony; Helquist, Brett (New York : HarperCollinsPublishers, 2001)
On the run after being falsely accused of murder, the three Baudelaire orphans find themselves in Heimlich Hospital, with the evil Count Olaf in close pursuit.
Keywords: Orphans -- Fiction; Humorous fiction